TARI PASAMBAHAN DAN FALSAFAH MINANG DALAM PERSPEKTIF ALIM ULAMA KOTA PADANG - Asriati, Afifah (Humanus, 2012)
The article aims to reveal the Padang Alim Ulama perspective toward Pasambahan Dance, in the context of Adaik Basandi Syara’, Syara’ Basandi Kitabullah (ABS-SBK) values. This research used qualitative approach based on teoritical perspective as conceptually embedded for reseach analysis. Interview and observation of some ulamas in Islamic organizations and higher institutions, as well as documentary techniques are used for data collecting. Data will be triangulated through member check and peer debriefing. The result shows that basically Pasambahan dance has been suited to the perspectives of the ulamas, based on the Minangkabau philosophy the ABS-SBK, both in the dancers’ moves and uniforms, although several things still needed to be fixed.Key words: Pasambahan dance, Minangkabau philosophy ABS-BSK, Padang ulamas